The application of optimal control techniques to macroeconomics : a survey - Palash, Carl J. (New York : Federal Reserve Bank of New York, 1979)
This paper discusses the development of optimal control as applied to macroeconomic stabilization problems. One of the purposes of this survey is to point out where additional work is still needed.
Includes bibliographical references: p. 25-29.
ne 11/08/2021
Loans
Keywords: Macroeconomics--Mathematical models; Control theory; Economic stabilization